(5x - 4)(3x + 5)
(5x - 4)(3x + 5)
(5x - 4)(3x + 5)
15x2-13x+2 = (5x-1)(3x-2) when factored
13x + 15 = 11x - 5 2x = -20 x = -10
7x-5+2x=3-4x+12 7x+2x-5=3+12-4x 9x-5=15-4x 9x+4x-5=15-4x+4x 13x-5=15 13x-5+5=15+5 13x=20 13x/13=20/13 x=20/13
15x-17
You have NOT equated the linear expression. However, equating to zer(0) 13x - 11y - 12 = 0 Then 11y = 13x - 12 y = (13/11)x - 12/11 Hence the slope is '13/11' and the intercept is '-12/11'. However, if you intended to write the expression as an equation 13x - 11y = 12 ( Note the '=/-' signs). Then 11y = 13x - 12 and we have the same equation. y = (13/11)x - 12/11
(3x + 5)(3x^2 + 4)
(3x - 4)(7x + 5)
13x
15x2 + 58x + 48= 15x2 + 18x + 40x + 48= 3x(5x + 6) + 8(5x + 6)= (3x + 8)(5x + 6)